Engaging with fragile states : an IEG review of World Bank support to low-income countries under stress - Carvalho, Soniya (Independent evaluation studies., 2006)
During fiscal 2003-05, World Bank lending and administrative budgets to fragile states amounted to 4.1 billion and 161 million, respectively. IEG's report assesses the effectiveness of this Bank support. The report finds that the Bank and the donor community have improved their operational readiness to engage with fragile states, and made substantial progress on donor coordination at the international policy level. Significant challenges remain, however. Donor agendas have been overly ambitious and need to be made more selective, the effectiveness of donor programs needs to be improved after t.